Algorithms on volume rendering - Yang, Yu Ting (2008)
Volume rendering is a technique to display 3D volumetric data sets as 2D images. Main computation in volume rendering includes classification, shading, resampling and compositing. The high computational consumption limited the use of volume rendering, especially on personal computers. In this thesis, we present a fast volume rendering algorithm that exerts the shear-warp factorization of viewing transformation upon an multi-resolution model of the original volume. Our algorithm supports interactive adjustment of classification and shading parameters with an immediate update rate in the rendering of a medium resolution volume (volume with about 2563 eight-bit voxels) on ordinary personal computers.